Communicating Environmental Risks: Local Newspaper Coverage of Shellfish Bacterial Contamination in Maine - Suldovsky, Brianne; Arbor, Eva; Skillin, Victoria; Lindenfeld, Laura (Frontiers in Communication, 2018)
Coastal resources play a vital role in Maine’s cultural and economic wellbeing, contributing an estimated 168 billion dollars to the Maine economy. There are numerous risks to the sustainability of Maine’s shellfishing industry and working waterfront, including pathogenic bacterial pollution. In this study, we ask a broad fundamental question central to science and environmental journalism: how do newspapers cover localized environmental risks and what are the implications of those approaches? Utilizing the northeastern U.S. state of Maine’s shellfishing industry as an exemplar environmental issue, this study examines how Maine’s two most read newspapers, the Bangor Daily News and the Portland Press Herald, report on bacterial contamination and shellfish. This study examines the themes that are present in the newspaper articles published about shellfish between 2003 and 2014 and analyzes the types of sources journalists used within their coverage of these issues. Overall, we identified seven key themes: economic concerns, environmental impacts, political and regulatory issues, issues of public health and safety, reference to cultural values, technical and infrastructural issues, and aesthetic concerns. The most commonly cited individuals in the articles were government officials and scientists. The least cited groups were clammers and shellfishermen, general citizens, advocacy groups, and worm diggers. Implications for local coverage of environmental risks in Maine, science communication, and sustainability science are discussed.